(untitled) (Research, Society and Development, 2020)
The objective of this study was to identify which variables of ingestive behavior, displacement patterns and pasture parameters explain most of the results among the levels of supplementation offered to Tifton-85 (Cynodon dactylon) heifers. Principal component analysis was used to identify which variables were relevant. In the analysis eight variables, grazing time, idle time, number of feeding stations/day, time per feeding station, bite rate/day, leaf blades mass, leaf allowance and leaf blade: stem ratio, explained 80.5% of the change in results. Heifers exclusively on pasture presented grazing time and bite rate/day and less idle time. Heifers receiving 0.4% supplementation visited more feeding stations, while heifers who received 1.2% supplement remained longer in feeding stations. In the first evaluation period, heifers had longer grazing time, number of food stations/day, bit rate, mass and allowance of leaf blades. The level of 0.8% of supplementary did not influence the variables evaluated. Displacement patterns and ingestive behavior of heifers receiving or not supplementation are influenced by the structural characteristics of the pasture.